Punishment of the Kanjuruhan Commotion due to Negligence from the Perspective of Causality Theory (Case of Decision 13/Pid.B/2023/PN Sby jo 922/K/Pid/2023) - Hidayatuzzakia, Hana; Masyhar, Ali; Wulandari, Cahya; Abu, Roziya (Universitas Negeri Semarang, 2023)
The consequences of the Kanjuruhan incident during Indonesian football matches prompted the implementation of punitive measures, aiming to ensure the protection of fundamental rights. The incident, which resulted in dissatisfaction among fans, particularly the Aremania supporters, was triggered by their team's defeat. The conclusion of the match saw a surge of discontent, leading fans to descend onto the field to express their disappointment. In conducting this research, a doctrinal legal approach, specifically of the normative type, was employed. The methodology involved a literature study, encompassing legal principles, rules, regulations, doctrines, theories, and legal dictionaries that contribute to legal literacy. The research aimed to gain insights into the necessity, harmony, and intentionality of legal measures, employing a scientific approach through doctrinal laws. The normative legal methods used positive law, context, and literature as their specifications. The research approach incorporated positive law and a case study method, focusing on the Kanjuruhan commotions. The findings and discussions unveiled the court's decision in accordance with Decision 13/Pid.B/2023/PN Sby, which acquitted the defendant. Legal efforts were subsequently initiated by the public prosecutor (JPU) in case 922/K/Pid/2023 to overturn the previous decision. The Supreme Judge determined a violation of Article 359 in conjunction with Article 360 of Law Number 1/1946 concerning Criminal Law Regulations, citing negligence leading to death. The causal link in this case was established when security forces (police) deployed tear gas into the spectator stands in response to the anarchic behavior of the Aremania supporters who had descended onto the field.